2006
DOI: 10.1177/112067210601600521
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Tear following Intravitreal Injection of Bevacizumab (Avastin)

Abstract: This report describes the development of retinal pigment epithelium tear after intravitreal bevacizumab injection. Future studies should be performed to evaluate which subtypes of lesions are most susceptible to this potential devastating visual complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Development of RPE tear has been reported after PDT and intravitreal anti-VEGF injections including bevacizumab and pegaptanib [2,4,5,7,8,10]. We are unaware of any report of RPE tear developing after intravitreal ranibizumab injection.…”
Section: Commentmentioning
confidence: 66%
See 1 more Smart Citation
“…Development of RPE tear has been reported after PDT and intravitreal anti-VEGF injections including bevacizumab and pegaptanib [2,4,5,7,8,10]. We are unaware of any report of RPE tear developing after intravitreal ranibizumab injection.…”
Section: Commentmentioning
confidence: 66%
“…Recently, cases of RPE tear following intravitreal anti-vascular endothelial growth factor (VEGF) injections including bevacizumab and pegaptanib have also been reported [2,4,7,8,10]. We report a patient who developed acute RPE tear following repeated intravitreal ranibizumab injections for occult CNV with PED due to AMD.…”
Section: Introductionmentioning
confidence: 82%
“…[1][2][3][4] Although the visual prognosis might be different in cases with spontaneous tears, where the choroidal neovascular membrane shows no regression, the rupture and displacement of the RPE might be a serious complication with the risk of visual damage. As serous pigment epithelial detachments (PED) associated with choroidal neovascularization (CNV) are often seen before an RPE tear, stretching forces on the weakened RPE were considered to play a causative role.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] Case series recently highlighted RPE tear increase after intravitreal bevacizumab treatment of neovascular AMD. [14][15][16][17][18][19][20][21][22][23][24][25][26] Chan et al 24 reported in a multicenter collective study 2.2% RPE tears in 1064 eyes. In a subgroup of 123 eyes with PED, 21 eyes (17.1%) had an RPE tear after intravitreal bevacizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In contrast, some cases of retinal pigment epithelial (RPE) tears after bevacizumab therapy have recently been reported. [15][16][17][18][19][20][21][22][23][24][25][26] Since intravitreal bevacizumab is a widely used therapy option for neovascular AMD, there is a need for further information on this topic. We analysed the occurrence of the RPE tear and the influence of related factors on this entity in a short-tem follow-up period following a single intravitreal bevacizumab administration for neovascular AMD.…”
Section: Introductionmentioning
confidence: 99%